Serum lipid and glucose profiles in HIV-positive Nigerian children - Olukemi O. Ige; Christopher S. Yilgwan; Augustine O. Ebonyi; Ruth Adah; Idris Adedeji; Esther S. Yiltok; Stephen Oguche; Fidelia Bode-Thomas (Elsevier, 2017)
Objectives: To describe the fasting serum lipid and glucose profiles of HIV-positive Nigerian children and determine the prevalence and risk factors for dyslipidaemia and hyperglycaemia, which are risk factors for cardiovascular diseases. Methods: This was a comparative cross-sectional study carried out at the Paediatric Infectious Disease Clinic (PIDC) of the Jos University Teaching Hospital (JUTH) for HIV-positive children and at two primary schools in Jos for HIV-negative children as controls. One hundred and forty-two HIV-positive children aged 6-18 years and an equal number of controls were studied by determining their fasting serum lipid and glucose levels. The prevalence of dyslipidaemia and hyperglycaemia was determined and their risk factors obtained using multivariate logistic regression. P values of less than 0.05 were considered statistically significant. Results: Mean triglyceride levels were significantly higher in HIV-positive children compared with controls at 87.2 mg/dL (95% confidence interval [CI] 79.4-95.0) and 68.1 mg/dL (95% CI 62.5-72.7), respectively (P<0.001). There were no significant differences in mean glucose levels. Dyslipidaemia was significantly higher in HIV-positive children (21.8%) compared with controls (12.7%; P=0.04). Total serum cholesterol was elevated in 17 (12.0%) HIV-positive participants compared with seven (4.9%) of controls (P=0.02). Children on lopinavir/ritonavir (LPV/r) and those with no significant or mild disease had a significantly higher prevalence of hypercholesterolaemia (33.3% vs 4.8% and 14.5% vs 0.0%, respectively; P<0.001). Conclusion: HIV-positive children on antiretroviral (ARV) drugs, especially LPV/r, should have their lipids regularly monitored as those with dyslipidaemia stand the risk of subsequently developing cardiovascular diseases.